Impregnated layer combustion synthesis of co doped ZnO green nanopigments: Using nature-based cellulosic templates. Issue 12 (15th June 2022) - Babaei, Arash; Norouzbeigi, Reza; Asaei, Sogol
Abstract: In this research, nanostructured green pigments of ZnO and Co (Cox Zn1-x O) were synthesized using impregnated layer combustion synthesis under microwave radiation. Taguchi design of experiments was employed to systematically investigate the influence of variables including the type of fuel, cobalt percentage, fuel to oxidizer ratio and type of template (impregnated active layer) to minimize the average crystallite size of particles. Three different types of fuels such as xylitol, mannitol and sorbitol as well as three templates containing filter paper, cotton and sterile gauze were used for the first time for synthesizing Cox Zn1-x O nanopigments. The optimum sample with the average crystallite size of 35 nm was synthesized in specific conditions including mannitol as a fuel, filter paper as a template, cobalt percentage of 7%, fuel to oxidizer ratio of 1.3× stoichiometry. XRD analysis demonstrated that whole samples have followed ZnO pattern representative pure phases in the final structure and well-doped Co 2+ . FESEM images revealed the homogeneity of the nanoparticles, with average particle size of 90 nm. As a result of colorimetric studies on the optimum sample a broad reflectance band nearby 520 nm demonstrates green region with L* = 58.19, a* = −13.65, C* = 14.35 and h° = 162.07. Results showed that the pigment calcination influences the reflectance intensity effectively (∼40%). Co percentage and template type are the most important factors affecting the final green product colorimetric properties. Graphical abstract: Image 1